Presence of women creators in the circuits of the current Spanish artistic industry - Izquierdo Expósito, Violeta; Zurbano Arrese, Erika (Historia y Comunicación Social, 2021)
Museum halls, art fair stands, award-winning lists and art books speak for themselves. Art is one of the areas where equality has not yet been reached. This work studies the imbalance that exists in this sector, always dominated by men, and confirms the path that remains to reach parity. This research aims to collect data from some of the most significant indicators in the artistic field to analyze and assess the presence of women in this industry. These parameters not only show the female representation in art, but also the visibility that is given to them from the institutions, as well as the recognition that they are granted and in which their work success is based on. The results of this work allow us to have a clearer photograph of the true position that women artists occupy in the current art scene in Spain.